Two tales:faith in Allah ,the beloved son - Khan, Saniyasnain (GoodwordKidz New Delhi, 2004)
The first tale highlights the steadfast faith of believers in Allah, demonstrating how trust in divine wisdom provides strength during challenges. The second story focuses on the profound love between a father and his son, illustrating themes of sacrifice and devotion in the pursuit of God's will.